Rick and Morty. RickleMania - Ellerby, Marc; Ellerby, Marc (Oni Press, 2025)
Wrestling fever has struck the Smith household! After stumbling across a wrestling channel on TV, Morty becomes obsessed with the Interdimensional Wrestling Federation and begs Rick to take him to one of their bare-knuckle brawls. While there, Jerry ends up signing an exploitative contract with the IWF's sponsor, PRO Energy Drink. Rick and Morty must break Jerry out of the contract, and the only way to do so is to enter the ring and fight their way out!